Comparing Men’s and Women’s Psychological Preparedness in Cangkringan for Mount Merapi Volcanic Eruptions - Sanger, A S C; Indra Nurpatria, N (KnE Life Sciences, 2019)
Mount Merapi is the most active and dangerous volcano in Indonesia with an eruption cycle of approximately five years. Eruptions are unpredictable, causing people who live around the mountain to be prepared for all outcomes. For example, the eruption in 2010 was particularly devastating and caused loss of lives, livestock, and homes, not only due to the eruption itself but also to people panicking during the evacuation process. Such panic could be reduced by ensuring that residents are psychologically prepared for future eruptions through enabling effective responses to natural disasters which have limited psychological impact and that prevent deaths while fostering resilience. The aim of this research was to determine the differences in psychological preparedness between men and women who live in Cangkringan, Sleman to face future Mount Merapi volcanic eruptions. Cangkringan was chosen because it experienced the most deaths during the 2010 volcanic eruption and because of its high potential for eruption exposure. Prior research has shown that gender is the only demographic variable that significantly affects psychological preparedness. Thus, the Kesiapsiagaan Psikologis Merapi (KPM) questionnaire was administered to 47 female participants and 43 male participants, and the results were statistically analyzed by using independent sample T-tests to compare psychological preparedness between men and women. The results showed that psychological preparedness for Mount Merapi volcanic eruptions among men and women in Cangkringan differ, which aligned with previous research. One contributing factor found was the difference in gender roles during times of disaster that were extensions of everyday gender roles. In their everyday lives, men’s roles mostly worked, either as farmers, coolies, employees, and so on. Meanwhile, women’s roles were related to household jobs, such as taking care of children and other family members, cooking, and so on. This difference caused different preparation, information, as well as a response while disaster between men and women. Keywords: psychological preparedness for natural disaster, gender, Merapi Mountain volcanic eruption